Kemampuan Profesional Guru Pendidikan Agama Islam dalam Implementasi dan Pengembangan Kurikulum Merdeka di Madrasah Ibtidaiyah Al-Ikhlas Kabupaten Nunukan - Bakhrul Ulum (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to analyze the competence of Islamic Religious Education (PAI) teachers in grade IV at Madrasah Ibtidaiyah (MI) Al-Ikhlas Nunukan in developing the Independent Curriculum. This research uses a qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The main focus of this research covers four aspects of teacher competence, namely pedagogic, professional, personality, and social, in the context of curriculum development that integrates Islamic values and differentiated and project-based learning (P5RA). The results of the study show that teachers have understood the basic concepts of the Independent Curriculum and have begun to apply them in learning practices. The pedagogic and professional competence of teachers seems to develop through the preparation of methods that are contextual and according to the needs of students. However, the preparation of teaching modules independently and the development of formative assessments are still the main challenges. The personality and social competence of teachers is also quite good, reflected in example, positive interaction with students, and active communication with parents and peers. This study recommends further training, assistance in the preparation of teaching tools, and increased collaboration between teachers as a strategy to strengthen the implementation of the Independent Curriculum at MI.